Financing Practices and Sustainability in Kenya’s Water and Sanitation Sector: An Empirical Study - Sharaf, Najiba; Bahez, Ayesha; Akhtary, Engila (Journal of Global Economy, Business and Finance, 2026)
Sustainability of water and sanitation services is categorized as a global problem. Water and sanitation is ranked top six in the UN’s seventeen sustainable development goals and an enabler to the achievement of all the other SDGs. Watsan sustainability involves improved access, acceptable water quality against growing demand. Access to watsan is a primary challenge globally due to its multifaceted nature. At the global level, Africa has the lowest freshwater resources at 9%, followed by Europe at 15.5%, then Asia at 28% while America has the highest (45%). Kenya is classified as a water scarce country. It is projected that rising water scarcity will cost an estimated 6% of the GPD by 2050 due to its impacts on agriculture, health and employment. Approximately, 53% of the population has no access to safe water while 77% have no access to improved sanitation thus making watsan access a national problem. Government spending on water development has significantly reduced from approximately Kshs46b in 2021 to Kshs.45b in 2022. The achievement of sustainability in the watsan, financing of up to 5 times the present level is needed. WASCOs continue registering high water loss annually resting at Kshs.11.2b in 2022. These statistics makes sustainability of water and sanitation in Kenya a gross national problem. Empirical studies shows that effective financial management practices contribute to firm sustainability. This study examined the influence of financing practices on sustainability of WASCO in Kenya guided by the pecking order theory. A positivism research philosophy was adopted with a descriptive research design. A sample of 46 companies was purposely selected from the 91 licensed WASCOs in Kenya. A likert scaled questionnaire was used to collect primary data. Secondary data was obtained using a secondary data collection sheet. Instrument reliability was assessed using the Cronbach’s alpha coefficient. Diagnostic tests included test of normality, test of outliers, tests of autocorrelation, multicollinearity and test of linearity using Q - Q plot, box plot, Durbin - Watson d statistics, Tolerance & VIF statistics and Pearson’s correlation coefficient respectively. A multiple linear model was employed for inferential analysis. Results show the model explained approximately 77.6% of WASCO sustainability. ANOVA show F - statistics of 48.515 with a p - value of 0.000 indicated existence of a statistically significant influence of financing practices on sustainability of WASCO. Beta coefficients results show β=13.761 for tariff financing followed by β=9.070 for debt financing and β= - 3.501 in the case of government financing. The study recommends prioritization of tariffs and debt financing options since they have a strong and positive influence on sustainability of these firms.